Understanding autism : from basic neuroscience to treatment - Moldin, Steven O.; Rubenstein, John L. R., 1955- (Boca Raton : CRC/Taylor & Frances, 2006)
Integrating basic and clinical neuroscience perspectives, this book presents a comprehensive perspective on state-of-the-art research in epidemiology, genetics, and clinical neuroscience and neural systems implicated in autism. This book seeks to stimulate new directions for autism research on etiology, pathophysiology, and the development of new drug treatment. An underlying theme focuses on the potential for future research given the availability of the human, mouse, and other genomes. The text also explores the role of autism in society, including health economics and advocacy issues of interest to legislators
Keywords: Autistic Disorder -- diagnosis; Autistic Disorder -- genetics; Autistic Disorder -- therapy